Enhancing Storage Efficiency: Class-Based Warehouse Layout Design of Indonesian Manufacturing Company - Tarigan, Yulinda; Elvrida Siagian, Chintya Vanesha (Politeknik Negeri Batam, 2025)
PT XYZ, a service firm focused on marine and offshore projects, encountered inefficient warehouse storage and the lack of an item code system. This made it harder to find and store items. The purpose of this study is to create a more efficient warehouse plan by utilizing the class-based storage strategy. The ABC analysis was used to classify 45 different sorts of items as fast, medium, or slow moving. The results revealed that this strategy boosted warehouse utility by 15.87%, reduced material movement distance by 19,586 meters, and saved cost by Rp49,454,650. Furthermore, picking and arranging things became more efficient, increasing by 0.38% and 0.22%, respectively.